2017
DOI: 10.1200/jco.2017.35.15_suppl.8018
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib-associated cardiovascular adverse events: A systematic review and meta-analysis.

Abstract: 8018 Background: The incidence and nature of cardiovascular adverse events (CVAEs) with carfilzomib (CFZ) in multiple myeloma (MM) remain incompletely defined. We performed the first systematic review and meta-analysis of CFZ CVAEs. Methods: PubMed was queried for the keywords “carfilzomib,” “Kyprolis,” and “PX-171.” Phase 1-3 clinical trials of carfilzomib in MM with evaluable toxicity data were included. CVAEs were defined as heart failure, hypertension, ischemia, and arrhythmia. All-grade and grade ≥3 CVAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 0 publications
3
60
0
2
Order By: Relevance
“…Cardiovascular adverse events are an important risk consideration with carfilzomib therapy. A systematic review and meta‐analysis of studies evaluating carfilzomib described a rate of grade ≥3 CVAEs in patients receiving carfilzomib doses of 45 mg/m 2 and higher of 11.9% . Our analysis yielded similar results with 11.1% of patients experiencing a grade ≥3 CVAE and an all grade occurrence rate of 25%.…”
Section: Discussionsupporting
confidence: 73%
“…Cardiovascular adverse events are an important risk consideration with carfilzomib therapy. A systematic review and meta‐analysis of studies evaluating carfilzomib described a rate of grade ≥3 CVAEs in patients receiving carfilzomib doses of 45 mg/m 2 and higher of 11.9% . Our analysis yielded similar results with 11.1% of patients experiencing a grade ≥3 CVAE and an all grade occurrence rate of 25%.…”
Section: Discussionsupporting
confidence: 73%
“…Carfilzomib treatment has been associated with cardiovascular AEs, including low rates of grade 3/4 cardiac failure, dyspnea, and hypertension. 32,33 However, in randomized phase 3 studies, the incidence of treatment discontinuation or death due to these cardiac events is low and comparable between treatment arms, highlighting the importance of control arms in elucidating treatment-related toxicities. 33 In this study, median LVEF remained stable, cardiac TEAEs were manageable and typically resolved, and no patient discontinued study treatment or died from cardiac TEAEs.…”
Section: Discussionmentioning
confidence: 99%
“…An independent meta-analysis of all published carfilzomib clinical studies (2623 patients from 25 studies) estimated grade $3 Exposure to study treatment in phase 3 trials 30 Higher cardiac event rates have been observed in some retrospective single-center studies, with doxorubicin exposure associated with increased risk. 31,32 Real-world data based on the MarketScan Claims database showed an ;3% incidence of hospitalizations due to cardiac AEs during carfilzomib treatment, validating the low rate of grade $3 CV AEs reported across carfilzomib clinical trials in real-world practice.…”
Section: Discussionmentioning
confidence: 99%